1985
DOI: 10.1115/1.3242473
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Criteria for Scaled LNG Sloshing Experiments

Abstract: This paper presents an overview of the current state-of-the-art in scale modeling of liquefied natural gas sloshing in ship tanks. The numerous potentially significant scaling parameters are discussed in detail and laboratory test data illustrating the effects of the important scaling parameters are presented. In view of current knowledge, an indication of appropriate scaling criteria is presented and recommendations for additional research efforts are outlined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
4

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 0 publications
1
26
0
4
Order By: Relevance
“…If viscous e!ects are important, then Re is kept constant by scaling viscosity for K " N . Bass et al [17] reported that for sloshing in tanks containing lique"ed natural gas, viscous e!ects were insigni"cant if Re number was larger than 10, and for such cases, viscous scaling need not be considered. Therefore, the liquid in the model absorber need only have the same density as the liquid in the prototype and a viscosity low enough to give a Reynolds number of greater than 10.…”
Section: On Practical Applicationmentioning
confidence: 98%
See 2 more Smart Citations
“…If viscous e!ects are important, then Re is kept constant by scaling viscosity for K " N . Bass et al [17] reported that for sloshing in tanks containing lique"ed natural gas, viscous e!ects were insigni"cant if Re number was larger than 10, and for such cases, viscous scaling need not be considered. Therefore, the liquid in the model absorber need only have the same density as the liquid in the prototype and a viscosity low enough to give a Reynolds number of greater than 10.…”
Section: On Practical Applicationmentioning
confidence: 98%
“…Bass et al [17] used Froude and Euler scaling to conduct experiments for liquid sloshing of 1/30th to 1/50th size of prototype tanks containing lique"ed natural gas. Muto et al [4] also used Froude scaling to represent liquid sloshing in a prototype tank with a 1/30th scale model using water as the working #uid.…”
Section: On Practical Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the other works published on liquid sloshing investigated the range of Reynolds numbers on the e!ect of viscosity of the liquid [5,6]. Another approach on the use of sloshing has been to use it as a means to control structural oscillations, such as in references [7}10].…”
Section: Introductionmentioning
confidence: 99%
“…Obtaining a detailed description of these experiments is often difficult due to the confidentiality of these studies. Berg (1987) and Olsen (1976) both for DNV and Bass et al (1985) studied the impact pressures in sloshing flows, as well as the very interesting and intricate issue of the scaling of sloshing experimental valúes to full scale. These studies suffered from limitations due to the limited recording and sampling capabilities of the data acquisition systems that were state of the art at that time.…”
Section: Introductionmentioning
confidence: 99%